Upaya penguatan kompetensi guru TPQ se-Kecamatan Mijen Kabupaten Demak melalui pelatihan evaluasi pembelajaran - Kuswanto, Edi; Mualimah, Siti (Penamas: Journal of Community Service, 2025)
The rapid development of Al-Qur'an Education Parks (TPQ) today is both a blessing and a challenge. The blessing is that many TPQ institutions will produce a Qur'anic generation. However, the challenge is how these institutions can produce a Qur'anic generation if they are not balanced with improvements in quality, both in terms of institutional management and teacher quality. The objective of this activity is to enhance the competencies of TPQ teachers in managing learning evaluations. The method used is Participatory Action Research (PAR) following Vincent II’s 9-step process: team formation, goal formulation, stakeholder identification, needs assessment and analysis, priority setting, preparation, implementation and monitoring, review and evaluation, and determination of new needs and objectives. The target of this activity is for TPQ teachers in Mijen Sub-district to be able to create effective learning evaluation administration. The results of the community service indicate that TPQ teachers can appreciate the importance of learning evaluation and are capable of creating standardized assessments using student achievement records. The implementation of this competency enhancement activity received a positive response from TPQ teachers, allowing for the development of future activities that can be more varied.